Anterior chamber tap cytology in acute postoperative endophthalmitis: a case–control study. Issue 6 (11th February 2021) - Leveziel, Loic; Knoeri, Juliette; Errera, Marie-Helene; Kobal, Alfred; Fardeau, Christine; Bouheraoua, Nacim; Sahel, José Alain; Baudouin, Christophe; Nordmann, Jean-Philippe; Baudouin, Françoise; Merabet, Lilia; Borderie, Vincent
Abstract : Aims: To determine anterior chamber tap cytology characteristics in acute postoperative bacterial endophthalmitis. Methods: 488 eyes of 488 patients were included in this retrospective case–control study. The study group included 93 eyes with bacteriologically documented endophthalmitis and 85 eyes with clinical endophthalmitis. The control group included 33 eyes with non-infectious postoperative inflammation, 116 eyes with acute uveitis and 161 cataract surgery eyes with no ocular inflammation. Cytological analysis, direct examination and microbiological cultures were performed in aqueous humour (AqH) samples. Inclusion criteria for the study group were the following: suspected endophthalmitis within 30 days following cataract surgery by phacoemulsification, secondary lens implantation, pars plana vitrectomy or intravitreal injection; best-corrected visual acuity (BCVA) <20/400; hypopyon or cyclitic membrane; absence of visibility of the retina; vitritis at a slit-lamp examination or in ultrasound B-scan. Results: Cell line counts (mainly polymorphonuclear neutrophils) were significantly higher in the two endophthalmitis study subgroups than in the three control subgroups. The study group showed a predominance of polymorphonuclear neutrophils as opposed to the three control subgroups including uveitis (p<0.00001). The best sensitivity/specificity was obtained using a polymorphonuclear neutrophil threshold of 10 per field (sensitivity, 0.90; specificity, 0.75). The sensitivity of the bacterial culture was 32% in the AqH. High neutrophil count was associated with poorer initial BCVA (rs =0.62; p<0.00001) and higher risk of retinal detachment during (p=0.04) and after (p<0.001) hospitalisation. Conclusion: Anterior chamber tap cytology is a quick and accessible tool complementary to culture and PCR for the management of acute postoperative endophthalmitis.